2021
DOI: 10.1371/journal.pone.0255309
|View full text |Cite
|
Sign up to set email alerts
|

Murine Type III interferons are functionally redundant and correlate with bacterial burden during influenza/bacterial super-infection

Abstract: Background Type III interferon, or interferon lambda (IFNλ) is a crucial antiviral cytokine induced by influenza infection. While IFNλ is important for anti-viral host defense, published data demonstrate that IFNλ is pathogenic during influenza/bacterial super-infection. It is known that polymorphisms in specific IFNλ genes affect influenza responses, but the effect of IFNλ subtypes on bacterial super-infection is unknown. Methods Using an established model of influenza, Staphylococcus aureus super-infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Studies examining the role of interferons during bacterial super-infection have shown that they enhance susceptibility. The mechanisms highlighted in these studies are due to decreased Type 17 immune activation and destabilization in function and recruitment of phagocytic cells (10, 11, 14, 17, 39, 53, 54). Our data suggests that at the time of super-infection, influenza memory experienced mice have reduced levels in expression of interferons, which based on prior studies would indicate that anti-bacterial mechanisms are preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the role of interferons during bacterial super-infection have shown that they enhance susceptibility. The mechanisms highlighted in these studies are due to decreased Type 17 immune activation and destabilization in function and recruitment of phagocytic cells (10, 11, 14, 17, 39, 53, 54). Our data suggests that at the time of super-infection, influenza memory experienced mice have reduced levels in expression of interferons, which based on prior studies would indicate that anti-bacterial mechanisms are preserved.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Furthermore, IFN-λs has an impact on immune cells in response to viral infection by limiting viral replication, lowering viral load, and delaying the development of viral drug resistance, resulting in the development of antiviral immunity. [14][15][16][17][18][19][20][21] Due to the scarcity of researches, the precise involvement of IFN-λs in non-viral inflammatory conditions is yet be precisely investigated. IFN-λs are primarily expressed by epithelial cells, but myeloid cells, neutrophils, B lymphocytes, and dendritic cells have also been found to express IFN-λs.…”
Section: Ifn-λs Regulatory Mechanismsmentioning
confidence: 99%
“…While multiple studies have shown that IFNλ increases the severity of super-infection, the specific mechanism by which this occurs is still being elucidated ( 11 , 74 , 76 , 77 ). IFNλ treatment during super-infection was shown to reduce neutrophil recruitment to the airways and neutrophil phagocytosis of both S. pneumoniae and S. aureus .…”
Section: Ifnλ In Super-infectionsmentioning
confidence: 99%
“…IFNλ treatment during super-infection was shown to reduce neutrophil recruitment to the airways and neutrophil phagocytosis of both S. pneumoniae and S. aureus . Further, IFNλ levels in BAL fluid of super-infected mice correlate positively with the bacterial burden ( 11 , 76 ). However, the influence of IFNλ on antimicrobial peptide (AMP) production is controversial: studies have been published showing no effect on AMP production after an IFNλ treatment and that IFNλR1 knockout mice have increased levels of several AMPs, including regenerating family member III gamma and neutrophil gelatinase associated lipocalin ( 76 , 77 ).…”
Section: Ifnλ In Super-infectionsmentioning
confidence: 99%
See 1 more Smart Citation